Urgensi Pendidikan Karakter dalam Upaya Pencegahan dan Pengendalian Perilaku Seksual Pra Nikah Remaja - Suwarno Suwarno (Sawwa: Jurnal Studi Gender, 2018)
The adolescent courtship and sexual behavior, and also gender-based violence against children continue to be a national concern because the condition is quite alarming. Surveys conducted by the Komisi Perlindungan Anak Indonesia/KPAI (Indonesian Child Protection Commission) and the Ministry of Health in 2013 mentions Indonesia 62.7% of adolescents have had sex outside of marriage, and 20% of the 94.270 women aged adolescents in Indonesia had become pregnant out of wedlock, and 21% of them had an abortion. This condition has been increasing vulnerability to various kind of health hazards especially related to reproductive and sexual health, including the growing threat of HIV/AIDS. This study aims to find out how dating and sexual behavior of adolescents in Central Java, and how to handle it. Using a survey method of 10,160 adolescents in Central Java in 2012-2016, the study found that in general, (an average of 67.2%) of adolescents declared that they were dating. While the form of expression of affection towards his courtship is done in various ways, including; holding hands (average 83.4%), lip kisses (average 20%), feeling / stimulating (average 6.7%), and even many have had sex outside of marriage (average 3.3%). If not done prevention and control efforts, it will have a long impact on the nation's resilience. This study recommends the importance of character education in the prevention and control of adolescent’s courtship and sexual behavior.